Fabrication of micrometer-scale porous gelatin scaffolds for 3D cell culture - Shim, Kyuyoung; Kim, So Hyun; Lee, Dongwook; Kim, Bumsang; Kim, Tae Hee; Jung, Youngmee; Choi, Nakwon; Sung, Jong Hwan (한국공업화학회, 2017)
In hydrogel scaffolds for 3D cell culture, porous structure plays a central role in maintaining cell survival by delivery of biochemical factors through the scaffolds. Thus, adequate pore structures should be a significant design factor for preparing cell culture scaffolds. Here, we present a non-cytotoxic approach to control porosity of a gelatin scaffold based on porogen leaching. Specifically, we fabricated photocrosslinkable hydrogel (gelatin methacrylate) containing porogens in a microfluidic channel, followed by dissolving out the porogens. Our approach allowed generation of micrometer-scale pores, increasing cell viability. This study could serve as a guide for tuning porosity of cell-seeded 3D scaffolds. (C) 2017 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.